Kedudukan Pengemudi Ojek Sebagai Mitra Kerja Dalam Perjanjian Pengangkutan Berbasis Aplikasi - Laisina, Steven; Kuahaty, Sarah Selfina; Lakburlawal, Mahrita Aprilya (PATTIMURA Law Study Review, 2025)
Application-based public transportation is a concept where public transportation services such as taxis, car sharing, or other public transportation are integrated and operated using application technology, especially mobile applications. Application-based public transportation is an innovation that brings many benefits to the community, both in terms of ease of access to transportation, increased security, and cost efficiency. The Partnership Agreement between the driver and the application company is referred to as a partnership agreement. The responsibility of the driver is adjusted to the losses of the consumer, Article 234 paragraph (1) of Law Number 22 of 2009 concerning Traffic and Road Transportation states that "drivers, motor vehicle owners, and/or public transportation companies are responsible for losses suffered by passengers and/or owners of goods and/or third parties due to driver negligence, This study shows that the position of application-based motorcycle taxi drivers as partners in transportation agreements has various legal and practical implications. Although this partnership offers flexibility and economic opportunities, there are challenges that must be faced regarding legal protection and driver welfare. Clear regulations and adequate protection are needed to ensure that application-based motorcycle taxi drivers can work safely and prosperously. Thus, the role of drivers as partners in transportation agreements can be optimized for the benefit of all parties involved. The responsibility of the driver is adjusted to the loss of the consumer. The creators and managers of the Maxim application help in the form of compensation that has been explained in the terms and conditions of Maxim in the responsibility regulations, the essence of which is that Maxim cares about the safety of application users by providing compensation according to the losses suffered by passengers.